Gambaran Klinis COVID-19 pada Mahasiswa FK Universitas Andalas Berdasarkan Status Vaksinasi COVID-19 - Hanif, Rayhendra; Suharti, Netti; Rasyid, Rosfita; Putra, Andani Eka; Russilawati, Russilawati; Izzah, Amirah Zatil (Fakultas Kedokteran, Universitas Andalas, 2024)
Background: COVID-19 is a disease caused by SARS-CoV-2 that’s highly infectious and has caused a pandemic. Vaccines are one of the most effective measures to control the spread of COVID-19. COVID-19 vaccines work by targeting the viral spike protein which can be varied in each variant of SARS-CoV-2 that threatens vaccines’ performance. This may allow breakthrough infection to occur with varying clinical characteristics. Objectives: This study aims to determine the clinical characteristics of COVID-19 on students at Medical Faculty of Andalas University based on their COVID-19 Vaccination status Methods: This research was observational descriptive. Data were collected using questionnaire with total sampling technique from December 2022 to January 2023 at the Medical Faculty of Andalas University. The questionnaire contained identity of respondent’s history, clinical characteristics of COVID-19 and their COVID-19 vaccination status. Questionnaire data were processed and displayed in frequency distribution tables. Results: The result showed that 100 samples out of 241 populations on this study were mostly women, mean age of 21.2 years old ± 0,7, range of age between 19-23 years old, most were already vaccinated for the third time, most were infected only once, and most infections happened after the second vaccination. The most common symptoms were fever, sore throat and cough. The severity of COVID-19 infections were relatively mild based despite of the vaccination status. No samples were reported of having severe critical illness. Conclusion: The symptoms of COVID-19 were relatively similar regardless of the vaccination status and the severity of COVID-19 infections were relatively mild regardless of the vaccination status on students at Medical Faculty of Andalas University.